The case of the fright flight - Steele, Michael Anthony (You choose. Scooby-Doo!, 2016)
During an airshow Scooby-Doo and the Mystery Inc. gang encounter a haunted World War II bomber plane--and it is up to the reader to decide how the mystery unfolds.